Civil Rights of the Believers of Unofficial Religions (Penghayat Kepercayaan) in Pekalongan District - Moh. Ilham A Hamudy; M Saidi Rifki (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2020)
There are seven groups of unofficial religions (penghayat kepercayaan) in Pekalongan District.  The issuance of Constitutional Court (MK) decision No. 97/ PUU-XIV/2016 did not automatically fulfill their civil rights.  There were various obstacles to implement the constitutional court decision. Therefore, this study specifically aimed to review their existence and the fulfillment of their civil rights after the Constitutional Court's decision. With a qualitative approach, and descriptive and literature methods, this study found that the social access of penghayat kepercayaan, such as the inclusion of  their beliefs in the religion part of the Identity Card ("KTP"), the availability of penghayat kepercayaan teachers at school, or marriage registration,  was yet to be fulfilled. The main obstacles were caused by the inadequate data collection of the penghayat kepercayaan population. Another obstacle was that, although the acceptance of the rest of the community towards the penghayat kepercayaan communities was quite good, the penghayat kepercayaan communities were still concern about them. Past discrimination seems to be main factor. For this reason, responsive works of the Pekalongan District Government are urgently needed to validate the data of penghayat kepercayaan communities and facilitate the social interactions across different communities to nurture a harmonious life in the district.